1996
DOI: 10.1136/bmj.312.7043.1393
|View full text |Cite
|
Sign up to set email alerts
|

Growth in utero and cognitive function in adult life: follow up study of people born between 1920 and 1943

Abstract: Objectives: To examine the relation between fetal growth and cognitive function in adult life. Design: A follow up study of men and women whose birth weights and other measurements of body size had been recorded at birth. Setting: Hertfordshire, Preston, and Sheffield. Subjects: 1576 men and women born in Hertfordshire, Sheffield, or Preston between 1920 and 1943. Main outcome measures: Intelligence quotient as measured by the AH4 test and amount of decline in cognitive function with age as estimated by the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
3
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 3 publications
2
48
3
2
Order By: Relevance
“…ities are in accordance with the majority of previous findings, 18,[26][27][28][29][30][31][32] and extend them in significant ways. Of the previous studies on children born at term, to our knowledge, 3 have focused solely on weight, 30-32 1 solely on head circumference, 18 and none on length or BMI at birth.…”
Section: Figuresupporting
confidence: 93%
“…ities are in accordance with the majority of previous findings, 18,[26][27][28][29][30][31][32] and extend them in significant ways. Of the previous studies on children born at term, to our knowledge, 3 have focused solely on weight, 30-32 1 solely on head circumference, 18 and none on length or BMI at birth.…”
Section: Figuresupporting
confidence: 93%
“…However, it is uncertain whether these factors also influence the rate and timing of cognitive decline later in life. For instance, the association between birth weight and cognitive function at 43 years was weak in the 1946 birth cohort despite associations with cognition from ages 8 to 26,2 whereas in a retrospective cohort of men and women in their 50s and 60s, the relation between birth weight and cognitive function was weak and non-significant 11. However, social circumstances in childhood remained important determinants of cognitive function among Finnish adult men, even after allowing for adult social circumstances 26…”
Section: Discussionmentioning
confidence: 98%
“…1 3 10 11 A study of sibship pairs found an increasing intelligence quotient at age 7 from 1500 to 3999 g birth weight 4. In a Scottish sample, cognitive function at 11 years was related retrospectively to birth weight, and in a Danish cohort of male conscripts aged up to 20, cognitive function increased across the range of birth weights up to 4.5 kg.…”
Section: Introductionmentioning
confidence: 99%
“…35 In pregnancies complicated by fetal growth restriction, this may lead to a proportionally smaller reduction in head circumference than body weight. 1,36,37 Martyn et al 38 suggested that, in the absence of an association between fetal growth and cognitive function, adaptations (including brain sparing) made by fetal growth-restricted infants seem to be largely successful in maintaining their brain development. However, results from another study suggest that cognitive development may be affected despite this brain-sparing effect.…”
Section: Discussionmentioning
confidence: 98%